Synthesis of 2-Amino-4-(2’-hydroxy-4’-isopropoxy-5’-bromophen-1’-yl)-6-substituted aryl Pyrimidine Derivatives and Related Compounds - Desai, J.A.; Desai, K.K. (Asian Journal of Chemistry, 2016)
2'-Hydroxy-4'-isopropoxy-5'-bromochalcones react with an alcoholic solution of guanidine nitrate in alkaline solution to give the corresponding 2-amino-4-(2'-hydroxy-4'-isopropoxy-5'-bromophen-1'-yl)-6-substituted aryl pyrimidines (2a–j). Compounds (2a–j) were converted to 2-phthalimido-4-(2'-hydroxy-4'-isopropoxy-5'-bromophen-1'-yl)-6-substituted aryl pyrimidines (3a–j) and 1-phenyl-3-[4'-(2"-hydroxy-4"-isopropoxy-5"-bromophen-1'-yl-6'-substituted aryl pyrimidine-2'-yl]-thiocarbamide derivatives (4a–j). All the synthesized compounds have been characterized by elemental analysis and spectral data.